2015
DOI: 10.1590/s1516-8913201500141
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Deterrent and Genotoxicity Analysis of a novel Phytopesticide by using Comet Assay against Helicoverpa armigera (HÜbner) (Lepidoptera: Noctuidae)

Abstract: Newly developed Phytopesticidal formulations from pongam and neem oils were evaluated for their feeding deterrent activity using leaf disc choice and no-choice methods, and genotoxic study using comet assay against Helicoverpa armigera at different concentrations of 5, 10, 15, and 20

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
1
5
0
1
Order By: Relevance
“… 19 and it was found that cadmium and lead caused large scale DNA damage in insect. Very few studies examined DNA damage in context of biocontrol 18 , 61 . Shetty et al .…”
Section: Discussionmentioning
confidence: 99%
“… 19 and it was found that cadmium and lead caused large scale DNA damage in insect. Very few studies examined DNA damage in context of biocontrol 18 , 61 . Shetty et al .…”
Section: Discussionmentioning
confidence: 99%
“…Raja et al (2005) identified two potential antifeedant compounds, namely 5-keto-pent-3, 4-enyl-2′phenol and 5-penty-methylene oxy-4, 4-dimethyl-cyclohexenol from H. suaveolens. Plant derived product Ponnem affected the DNA of H. armigera which was confirmed by comet assay ( Packiam et al, 2015 ). Two new oil formulations, namely neem oil, karanj oil and caryophyllene isolated from ethyl acetate extract of Hyptis suaveolens and neem oil, karanj oil and β-sitosterol isolated from ethyl acetate extract of M. Corchorifolia showed pest control properties at the laboratory condition ( Pavunraj et al, 2016 ).…”
Section: Introductionmentioning
confidence: 82%
“…To determine the toxicity of the essential oils, the leaf-dipping technique was followed [14] . To determine the lethal concentration(LC 50 ) and LC 90 , five concentrations were prepared in distilled water using 0.5% Triton™ X-100 (Sigma-Aldrich Corp., St. Louis, MO, USA), as a surfactant.…”
Section: Toxicity Assay Of the Plant Essential Oilsmentioning
confidence: 99%
“…DNA damage also was estimated in Culex quinquefasciatus using essential oil of Psoralea corylifolia with larvicidal and adulticidal effect [13] . Moreover, DNA damage and mutation were detected in H. armigera and Rhyzopertha dominica treated with various plant oils [14] .…”
Section: Introductionmentioning
confidence: 99%